Reduksi bahan organik (amonia) pada air limbah menggunakan limbah bulu ayam sebagai alternatif adsorben - Izmah, Azatil; Suprayogi, Dedy; Nengse, Sulistiya (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2023)
Poultry industry waste products produce solid waste as a chicken feathers and liquid waste as a water used for processing meat. Disposal of this waste can cause pollution to the environment and living things because it contains ammonia. This research aims to determine the adsorption efficiency and the adsorption capacity of the adsorbent. The adsorbent was made using chicken feather waste which had been activated using HCl. The experiment used the batch system method with a speed of 150 RPM with a variation of the adsorbent mass of 1 gram, 2 grams and 3 grams with a time of 90 minutes. Ammonia levels in each sample were measured with a UV-VIS spectrophotometer. The results showed that the best adsorption capacity was using 1 gram of adsorbent mass with an efficiency level of 86.78% and an adsorption capacity of 31.97 mg/gram.